Perception and Motivation of Farmers in the Development of Natural Silk Business in Soppeng Regency Sulawesi Selatan - Wahyudi , Wahyudi Isnan; Nurhaedah , Nurhaedah Muin; Hayati, Nur Hayati (Forestry Department, University of Muhammadiyah Makassar, 2019)
The development of natural silk has not been optimal because the handling of the problem tends to be general and not adjusted to the socio-economic characteristic of the community. In Soppeng Regency, natural silk is carried out by diverse socio-economic backgrounds of the community that can influence perceptions and motivations in the development of natural silk business. This study aimed to determine the perceptions and motivations in developing natural silk business which is expected to be a formulation material in the preparation of natural silk business policies. The study was conducted in Donri-Donri District as the center of natural silk development in Soppeng Regency. Data collection used survey method and interview. The sampling of respondents used a random sampling method for natural silk farmers. The results of the study indicate that in Soppeng District, the high farmer’s perception of natural silk business are related to socio-economic factors such as the length of residence in the village and gender. The motivation of farmers in natural silk business is generally because natural silk business is easy to implement, technological mastery, and easy to obtain information. Natural silk have big chance to be developed with quality improvement of silkworm seed and silkworm feed. High perception and motivation of community need to be accompanied by the availability of supporting factors so that this business can develop optimally.